Gender Disparities in Climate Resilience: Amplifying Voices of Women in Climate Change Issue in Indonesia’s Chairmanship of ASEAN 2023 - Anggraheni, Palupi; Hanura, Marten; Subhan, Muhammad; Setyaningsih, Dewi; Diaz, Yohana Grezia (Parahyangan Center for International Studies, 2024)
Indonesia officially received the mandate as Chair of ASEAN from January 1 to December 31, 2023. During the post-COVID-19 pandemic, in the period 2022-2023 Indonesia received appreciation from the international community regarding the successful organization of international forums including the G-20. Indonesia's attitude is considered to remain neutral and maximize Indonesia's function as a middle-power at the level of multilateralism, amid geopolitical conflicts such as the Ukraine-Russia conflict and regional instability in the Middle East. But on the other hand, there are other issues in the realm of low politics, including the issue of climate change and women's vulnerability. As a region with a long coastline, it has a high potential risk as a chain effect of climate change. In addition, the gender disparity that is still quite high in this region is one of the factors that make women vulnerable to climate change issues, such as vulnerability in the labor, health and gender-based violence sectors. This paper focuses on seeing the extent to which Indonesia's role as chair of ASEAN in 2023 advocates the issue of climate change in a gender framework. The concept of Gender Equality and Social Inclusion (GESI) which focuses on women's participation in the public sector and policy initiation is used as a framework. The expected results of this study can show the relationship between environmental issues and women's vulnerability and the imbalance between women's participation in the public sector and policy initiation. Keywords: GESI, women, climate change, ASEAN Chairmanship, Indonesia.